2004
DOI: 10.1111/j.1475-6773.2004.00228.x
|View full text |Cite|
|
Sign up to set email alerts
|

A Longitudinal Examination of Hospital Registered Nurse Staffing and Quality of Care

Abstract: Objective. To evaluate previous research findings of the relationship between nurse staffing and quality of care by examining the effects of change in registered nurse staffing on change in quality of care. Data Sources/Study Setting. Secondary data from the American Hospital Association (AHA)(nurse staffing, hospital characteristics), InterStudy and Area Resource Files (ARF) (market characteristics), Centers for Medicare and Medicaid Services (CMS) (financial performance), and Healthcare Cost and Utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 179 publications
(193 citation statements)
references
References 21 publications
(27 reference statements)
9
181
1
2
Order By: Relevance
“…Nurses who work in rural hospitals also differ from their urban counterparts in work patterns and commuting behavior (Skillman, Palazzo, Keepnews, & Hart, 2006), both of which have been linked to nurse safety outcomes (Sveinsdóttir, 2006;Trinkoff, Le, Geiger-Brown, Lipscomb, & Lang, in press). Managed care (i.e., HMO) penetration was included because it has provided the impetus for numerous nursing unit re-design efforts like the introduction of professional practice models and changes in nursing skill mix that affect utilization of nursing personnel, staffing adequacy (Hoover, 1998;Mark, Harless, McCue, & Xu, 2004;Mark, Salyer, & Wan, 2003) and, ultimately, safety. Finally, because there is substantial regional variation among hospitals in illness treatment, volume and complexity of procedures performed, and resource consumption (Wennberg & Gittlesohn, 1973;Wennberg, Freeman, & Culp, 1987), we included geographic region as a variable.…”
Section: Organizational Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses who work in rural hospitals also differ from their urban counterparts in work patterns and commuting behavior (Skillman, Palazzo, Keepnews, & Hart, 2006), both of which have been linked to nurse safety outcomes (Sveinsdóttir, 2006;Trinkoff, Le, Geiger-Brown, Lipscomb, & Lang, in press). Managed care (i.e., HMO) penetration was included because it has provided the impetus for numerous nursing unit re-design efforts like the introduction of professional practice models and changes in nursing skill mix that affect utilization of nursing personnel, staffing adequacy (Hoover, 1998;Mark, Harless, McCue, & Xu, 2004;Mark, Salyer, & Wan, 2003) and, ultimately, safety. Finally, because there is substantial regional variation among hospitals in illness treatment, volume and complexity of procedures performed, and resource consumption (Wennberg & Gittlesohn, 1973;Wennberg, Freeman, & Culp, 1987), we included geographic region as a variable.…”
Section: Organizational Contextmentioning
confidence: 99%
“…Availability of support services was measured using a checklist in which nurses rated 27 support services as not available, inconsistently available, or consistently available, with higher scores indicative of greater availability (Mark, 1992;Mark et al, 2003). Patient acuity was measured using a 14-item Likert-type questionnaire developed by Overton, Schneck and Hazlett (1977) and twice revised by Mark (Mark, 1992,Mark et al, 2004. Nurses were asked to estimate the proportion of patients on their unit who had complex problems (e.g., how many patients require the use of technical equipment, medications through central venous lines, or frequent monitoring).…”
mentioning
confidence: 99%
“…More recent studies have found that hospitals with high nurse-to-bed ratios had lower than expected mortality rates . And several studies that have had the relationship between nurse staffing and mortality as their primary focus have found ''better'' nurse staffing associated with lower in-hospital mortality (Aiken et al 2002;Mark et al 2004), although Needleman et al (2002) found no relationship to mortality. Four studies have provided support for the relationship between higher levels of nurse staffing and shorter length of stay (ANA 1997(ANA , 2000Lichtig, Knauf, and Milholland 1999;Mark, Harless, and McCue 2005;Needleman et al 2002).…”
Section: Mortality and Length Of Stay In For-profit And Not-for-profimentioning
confidence: 99%
“…Hospitals with staffing outliers also were excluded. Additional exclusions were for hospitals with fewer than 15 expected mortalities (Mark et al 2004). These exclusions resulted in a sample of 48 FP hospitals and 268 NFPs in 1990, and 44 FPs and 266 NFPs in 1995.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation